Ligamentum flavum hypertrophy animal models: methodological trade-offs and future directions - Chen, Long; Zhang, Wanxia; Zhang, Yu; Gong, Qin (Frontiers in Veterinary Science, 2025)
Ligamentum flavum hypertrophy (LFH) represents a key pathological factor in lumbar spinal stenosis (LSS), which is characterized by abnormal collagen deposition, reduced elastin fibers, and other degenerative changes. LFH compresses the spinal cord and nerve roots, causing symptoms like low back pain, numbness, and intermittent claudication, and may lead to central spinal stenosis, with significant consequences for quality of life. The pathophysiology of LFH involves extracellular matrix remodeling, inflammatory mediator release, and biomechanical stress, which contribute to spinal canal narrowing and nerve root compression. Although known risk factors such as age, obesity, and mechanical load have been identified, the exact mechanisms remain unclear. Well-established animal models are essential for understanding LFH and developing therapeutic strategies. This paper compares four major LFH animal models—surgical, biomechanical, chemical induction, and hybrid models—with evaluation of their clinical relevance, technical feasibility, cost-effectiveness, and limitations. Recommendations are provided for improving these models to enhance preclinical and clinical application.